Theodor W. Adorno - Ästhetische Theorie - Eusterschulte, Anne 1964-; Tränkle, Sebastian (Klassiker auslegen, 2021)
In Aesthetic Theory, Theodor W. Adorno laid out the final aesthetics of modernity, which, at the same time, is a reflection on the societal conditions of art after Auschwitz. The contributors of this volume disclose the conceptual and material contexts of the reflections, while examining the history of their impact and current relevance